Making Islamic University and Madrasah as Society's Primary Choice - Abuddin Nata; Ahmad Sofyan (Al-Hayat Al-Istiqomah Foundation, 2020)
Islamic university and Islamic-Based School (madrasah) in Indonesia can be the primary choice of society if adequately managed through the right strategic programs and efforts. This study used field and literature data. This study proved that since 1970 Islamic University and Madrasah became the choice of the upper-middle-class Muslim community. This situation can increase or decrease, depending on reliable teamwork that is willing to work with commitment and high moral responsibility.